Evaluation of the Suitability of Using Anticholesterol Drugs in Cholesterol Patients at Sekip Public Health Centre Palembang - Dhiny Zsa Zsa Aulia; Tahoma Siregar; Ritha Widyapratiwi (Journal of Tropical Pharmacy and Chemistry, 2023)
Dyslipidemia is a condition that increases plasma cholesterol, LDL, and triglyceride levels, decreases HDL levels, or causes a combination of abnormalities. In amounts sufficient for what the body needs, cholesterol works to produce hormones, vitamin D, and other components. Cholesterol is produced by the liver and can also be found in animal products. This study aims to determine the profile of treatment and the suitability of the use of anticholesterol drugs in patients with high cholesterol at Sekip Public Health Centre Palembang. This research is non-experimental, using quantitative methods and 40 samples. The demographic results of the total cholesterol levels of patients who experienced a decrease were 100 patients (100%). Demographics of patients by gender: mostly female, as many as 30 patients (75%). Demographics of patients by age: mostly in the age category 56–65 years, as many as 16 patients (40%). Demographics of patients based on comorbidities: the most common was diabetes mellitus, with as many as 12 patients (30%) The highest use of anticholesterol drugs is in the statin group, namely simvastatin (100%). The suitability of the selection of anticholesterol drugs was 100% for 100 patients. The suitability of the selection of the anticholesterol dose in 100 patients (100%)